2000
DOI: 10.1038/sj.ejcn.1601107
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of the 24-hour diet recall calibration method used in the European Prospective Investigation into Cancer and Nutrition (EPIC): general concepts and preliminary results

Abstract: Objectives: Despite increasing interest in the concept of calibration in dietary surveys, there is still little experience in the use and standardization of a common reference dietary method, especially in international studies. In this paper, we present the general theoretical framework and the approaches developed to standardize the computer-assisted 24 h diet recall method (EPIC-SOFT) used to collect about 37 000 24-h dietary recall measurements (24-HDR) from the 10 countries participating in the European P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
352
0
10

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 324 publications
(364 citation statements)
references
References 57 publications
2
352
0
10
Order By: Relevance
“…In order to standardize information on the consumed food items across countries, systematic questions used for describing a given food were asked, eg cooking method, brand name or fat content. These characteristics of foods were described by socalled 'facets' (Slimani et al, 2000). For each facet a set of 'descriptors' was defined, allowing specifying the facet more precisely.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to standardize information on the consumed food items across countries, systematic questions used for describing a given food were asked, eg cooking method, brand name or fat content. These characteristics of foods were described by socalled 'facets' (Slimani et al, 2000). For each facet a set of 'descriptors' was defined, allowing specifying the facet more precisely.…”
Section: Methodsmentioning
confidence: 99%
“…When a person reported eating a special meat or fish item, questions (facets) on cooking methods were automatically prompted on the screen with several possible pre-defined answers (descriptors). If a person was not able to answer the question precisely, 'not specific' cooking methods could be chosen (Slimani et al, 2000). The cooking method 'fried' was used as a generic descriptor in EPIC-SOFT.…”
Section: Methodsmentioning
confidence: 99%
“…Questionnaire evaluating FIRSSt. (13) Examine the level of standardisation of a computer-assisted 24HR (EPIC-SOFT).…”
Section: Continuedmentioning
confidence: 99%
“…However, the EPIC study results showed problems still existed in the standardisation of the multiplepass 24HR. Further research was needed to compare the actual validity of 24HR intakes across centres using urinary N 2 and K as gold standards, so as to estimate the magnitude of systematic measurement errors across the EPIC centres (13) .A disadvantage of self-administered computerised assessment is that it requires the user to have a minimum level of knowledge about computer use. Certain population groups may have difficulty using a computerised assessment tool, for example, older and less educated individuals (7) .…”
mentioning
confidence: 99%
“…The 24 h recall requests information on all foods being eaten the day before with specifications regarding amount and type of food. The instrument has already been tested and applied in ten European countries (Slimani et al, 2000) and seems to be applicable to all study populations in Europe (Slimani & Valsta, 2002). The version being applied is based on a highly standardized computer program and on a common food list.…”
Section: Introductionmentioning
confidence: 99%